REFORMULASI SANKSI PIDANA TERHADAP PENGGUNA PENGGUNA PIL PCC (PARACETAMOL, CAFFEINE DAN CARISOPRODOL) DALAM HUKUM PIDANA INDONESIA - Ade Satria Habibillah; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Drug abuse is a drug that is misused (misused) every time someone with arbitrary use of drugs (suchas when a drug is prescribed for someone else). Pills are abused (absed) when a person continues toconsume the drug, resulting in physical and psychological dependence on the drug. PCC pills (Paracetamol,Caffeine, and Carisoprodol) are drugs that can be used to relieve pain and heart pain medications, so thesedrugs should not be taken carelessly under the supervision,of doctors and pharmacists.Perpetrators of misuse of the PCC pill must be able to take responsibility for their actions. Thisstudy raises the issue of what is the urgency of formulation policies for users as well as the ideal legal policyfor PCC users (Paracetamol, Caffeine, and Carisoprodol)The research method used is normative research with a statutory approach, fact approach and legalconcept analysis approach. The results of this study indicate that pcc pills that have been designated asclass 1 narcotics according to the Minister of Health Regulation are immediately included in Law Number35 of 2009 concerning Narcotics. Perpetrators of misuse of pcc pills are responsible for their actions byundergoing rehabilitation sanctions.Keywords: Accountability, PCC, Legal Arrangements.